2017
DOI: 10.1016/j.fsigen.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Length and repeat-sequence variation in 58 STRs and 94 SNPs in two Spanish populations

Abstract: We have genotyped the 58 STRs (27 autosomal, 24 Y-STRs and 7 X-STRs) and 94 autosomal SNPs in Illumina ForenSeq™ Primer Mix A in 88 Spanish Roma (Gypsy) samples and 143 Catalans. Since this platform is based in massive parallel sequencing, we have used simple R scripts to uncover the sequence variation in the repeat region. Thus, we have found, across 58 STRs, 541 length-based alleles, which, after considering repeat-sequence variation, became 804 different alleles. All loci in both populations were in Hardy-W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…This type of inconsistency between alleles and sequences was reported by Novroski et al 34 Moreover, discrepancies in SB allele nomenclature could be observed when using different coordinates of sequence guides and analysis tools. In previous studies of SB alleles, some researchers followed the nomenclature recommended by ISFG 21 , while others used custom-defined nomenclature 36,37 . Discordant nomenclatures can lead to inconsistent allele calling between laboratories, further confusing precise allele and InDel calling between populations.…”
Section: T a T C A A T C T G T C G A T Amentioning
confidence: 99%
See 1 more Smart Citation
“…This type of inconsistency between alleles and sequences was reported by Novroski et al 34 Moreover, discrepancies in SB allele nomenclature could be observed when using different coordinates of sequence guides and analysis tools. In previous studies of SB alleles, some researchers followed the nomenclature recommended by ISFG 21 , while others used custom-defined nomenclature 36,37 . Discordant nomenclatures can lead to inconsistent allele calling between laboratories, further confusing precise allele and InDel calling between populations.…”
Section: T a T C A A T C T G T C G A T Amentioning
confidence: 99%
“…A pair-ended sequencing will be performed after the library preparation and then the raw data will be imported to UAS to analyse automatically. Validations using the ForenSeq Signature system have demonstrated its advantages in forensic practice relative to other library preparation kits [29][30][31][32][33] , but the knowledge of alleles and genotype frequencies of these 58 STRs is still inadequate for accurate lineage analysis [34][35][36][37][38][39] and is not sufficient for population genetic studies, which limits its utility in forensic casework.…”
mentioning
confidence: 99%
“…We performed six sequencing runs in a standard flow cell, with 22, 88, 96, 96, 94 and 96 samples, and one run in a micro flow cell with 16 samples, plus the manufacturer-supplied positive and negative controls in each run. STR allele sequences were retrieved from the report generated by the Forenseq UAS interface and inspected by means of an in-house R script (IFator for autosomal STRs, YIFator for Y-STRs, and XIFator for X-STRs, available from github https://github.com/ fcalafell/) [17] . These scripts allow uncovering much more sequence diversity than that reported by the Forenseq UAS interface, which only highlights sequence variants when they are found in isometric heterozygotes, that is, in individuals carrying two alleles of the same length but different sequence.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the Verogen Forenseq™ Primer Mix A (Verogen, San Diego, CA) ,which contains 58 STRs and 94 SNPs, together with the with the Universal Analysis Software (UAS) provided by the manufacturer yields for each successful genotype two different types of information: a length-based (LB) genotype, in accordance with the numeric genotype that sizing by capillary electrophoresis would have yielded, and a repeat-sequence based genotype (RSB), that is, the sequence haplotype of the repeat region of each STR (the flanking region sequence is not available through the UAS). A number of studies [17][18][19][20], among others, have shown that, while the overall informativeness (as measured by a priori statistics) increases moderately from LB to RSB genotypes, the number of different alleles and the number of rare alleles register more substantial increases.…”
Section: Introductionmentioning
confidence: 99%
“…Devesse et al (2018) documented sequence-specific STR allele frequencies for 400 samples from the white British and British Chinese ethnic groups. Others have completed various population studies with the MFGS for diverse populations such as; Qatari (Almohammed, Iyengar, Ballard, Devesse, & Hadi, 2017), Spanish (Casals et al, 2017), Singaporean (Ramani, Wong, Tan, Shue, & Syn, 2017), Taiwanese (Hwa et al, 2019), and the 944 individuals of the CEPH human genome diversity panel (Phillips et al, 2018). Jäger et al (2017) published species specificity testing as part of the developmental validation.…”
Section: Population Studiesmentioning
confidence: 99%